English English: English - Amanda Dwi Yuliantiaji; Yanti Puji Astutie; Aminul Fajri (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the relationship between environmental cost, profitability, industry group, and environmental disclosure among industrial companies listed on the Indonesia Stock Exchange during 2021-2025, while controlling for firm size, leverage, and firm age. Secondary data were collected from annual and sustainability reports and analyzed using Kendall’s Tau-b in IBM SPSS Statistics 26. The findings indicate that environmental cost is positively and significantly associated with environmental disclosure, whereas profitability, industry group, firm size, leverage, and firm age show no significant relationship. Environmental disclosure is therefore more closely linked to firms’ environmental spending. Keywords: Environmental Cost; Environmental Disclosure; Industry Group; Legitimacy Theory; Profitability